Profil Kemampuan Pemahaman Bahasa Lisan pada Lansia di Kelurahan Mojosongo - Jusy Falisa; Setyadi Nugroho; Sudarman Sudarman (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Elderly individuals undergo various physical, cognitive, and social changes that directly impact their communication skills, particularly in oral language comprehension. This ability is crucial for maintaining the quality of social interactions and ensuring adequate access to healthcare information. Objectives: The objective of this research is to investigate the oral language comprehension profiles of elderly residents in Mojosongo. The assessment focuses on general proficiency and specific performance across word and sentence levels—categorized by the elderly age group—using the TADIR (Aphasia Test for Diagnosis, Information, and Rehabilitation) instrument. Methods: A quantitative descriptive design was employed. The study included 30 older adults aged 60–74 years who were selected through purposive sampling based on predefined inclusion criteria. Results: Of the 30 participants, 5 individuals (16.7%) demonstrated impaired comprehension, 15 individuals (50.0%) showed mild impairment, and 10 individuals (33.3%) exhibited normal comprehension. The overall mean score was 4.17, indicating mild impairment. Word-level comprehension exceeded sentence level performance, with both groups showing a mean score of 1.67 at the sentence level. These results suggest persistent challenges related to syntactic integration, semantic processing, and working memory. Conclusion: Although most older adults retained functional communication abilities in daily contexts, mild limitations were evident, particularly in understanding complex sentences. These findings underscore the need for communication strategies that are linguistically accessible and supportive of age related cognitive changes. Keywords: Elderly, Spoken Language Comprehension, TADIR, Mojosongo.